Pengaruh Family Support dan Peer Support terhadap Career Decision Self-Efficacy Atlet yang Berkuliah di Fakultas Olahraga dan Kesehatan Undiksha - Ketut Ngurah Arya Yudistira; Ni Made Dwi Ariani Mayasari (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to examine the influence of family and peer support on the career decision-making self-efficacy of athletes studying at the Faculty of Sports and Health, Undiksha. This study applied a causal quantitative approach involving 60 athletes as respondents through a saturated sampling technique. Data were collected using a Likert-sized questionnaire that had met validity and reliability tests, then analyzed using linear multiple regression. The results of the analysis showed that both family and peer support partially had a positive influence on athletes' beliefs in career decision-making self-efficacy. However, family support was the variable that had a more dominant influence on career decision-making self-efficacy compared to peer support. Emotional support was the most dominant aspect of family support, which was reflected in the provision of motivation, empathy, and a sense of security from the family. In terms of peer support, emotional support from peers was the main factor in strengthening individual self-confidence and was supported by shared experiences. The magnitude of the influence of family support had an impact on increasing athletes' ability to understand their potential (self-appraisal), so they would be more confident and better prepared in determining career choices. So that family support and peer support in harmony have an equally important role in strengthening the athlete's self-efficiency career decisions.